Long-term glucocorticoid treatment in patients with polymyalgia rheumatica, giant cell arteritis, or both diseases: results from a national rheumatology database - Albrecht, K.; Huscher, D.; Buttgereit, F.; Aringer, M.; Hoese, G.; Ochs, W.; Thiele, K.; Zink, A. (Rheumatol Int, 2018)
The objective of this study was to evaluate glucocorticoid (GC) use in patients with polymyalgia rheumatica (PMR), giant cell arteritis (GCA) or both diseases (PMR + GCA) under rheumatological care. Data from patients with PMR (n = 1420), GCA (n = 177) or PMR + GCA (n = 261) from the National Database of the German Collaborative Arthritis Centers were analyzed regarding GCs and related comorbidities (osteoporosis, diabetes and cardiovascular disease), stratified by disease duration (DD). Longitudinal data were analyzed for all patients with a DD </= 2 years at database entry (n = 1397). Three-year data were available for 256 patients. Predictors of GC use >/= 3 years were examined by logistic regression analyses. A total of 76% received GCs, and 19% (PMR) to 40% (GCA) received methotrexate. Median GC doses were 12.5 mg (PMR), 11.3 mg (GCA), and 20.0 mg/day (PMR + GCA) in a 0-6-month DD. Median GC doses </= 5 mg/day were reached at a 13-18-month DD in PMR patients and at a 19-24-month DD in GCA or PMR + GCA patients. In the multivariate analysis, baseline methotrexate (OR 2.03, [95% CI 1.27-3.24]), GCs > 10 mg/day (OR 1.65, [1.07-2.55]), higher disease activity (OR 1.12, [1.02-1.23]) (median 0.6 years DD), and female sex (OR 1.63 [1.09-2.43]) were predictive for GC therapy at >/= 3 years. Of the examined comorbidities, only osteoporosis prevalence increased within 3 years. GC use for >/= 3 years was reported in one-fourth of all the patients. A difficult-to-control disease activity within the first year was a good predictor of long-term GC need.